Деякі аспекти ярмаркування на Полтавщині в документах - Дроздова, Олена (Видавництво Львівської політехніки, 2012)
This article deals with the fair development in Poltava region at the second half of XVII – XVIII centuries and its fragmentary displaying in different documents.
Keywords: ярмарки; торговельні заклади; продавці; покупці; Полтавщина; торговельні договори